Intuition and decision making - Hogarth, Robin M. (Henry Stewart Talks, 2011)
Quotes about intuition, How do we make decisions?, Deliberate thought vs. intuition, Some examples, What is intuition?, Two systems of thought, Intuition defined, Learning from experience, Kind and wicked learning structures, Intuition and expertise, How good is intuition?, When should you trust intuition?, How to educate your intuition